Amiodarone Induced Thyrotoxicosis and Treatment Complications in a Man With Cyanotic Congenital Heart Disease: A Case Report - Chua, Marvin Wei Jie; Mok, Shao Feng (Frontiers in Cardiovascular Medicine, 2020)
Background and Case: Amiodarone induced thyrotoxicosis (AIT) is a potentially life-threatening condition with two main subtypes. This case report describes a patient with cyanotic congenital heart disease, who developed AIT with severe biochemical thyrotoxicosis. Due to complications to corticosteroids and thionamides, second-line treatment with cholestyramine and lithium was given which eventually restored euthyroidism, averting the need for thyroidectomy and its associated risks. Due to the presence of both typical and unusual features, the final diagnosis of AIT Type 2 (AIT-2) could only be retrospectively elucidated after a prolonged clinical course. Conclusion: Corticosteroids are well-recognized to be the first-line treatment for AIT-2. This case illustrates a rare phenomenon: successful treatment of AIT-2 with lithium and cholestyramine. In patients who develop complications from first-line therapy, prompt treatment with alternative agents may successfully avert thyroidectomy and its associated risks.